Devenir « personne-ressource » : gestes professionnels emblématiques d'une posture d'ajustement d'enseignants spécialisés - Bruno Grave
Specialized teachers, with the CAPPEI reform (2017), perform a resource person function. This activity turns out to be complex and commits these professionals to permanently adjust to the situation and to build a posture and professional adjustment gestures (Bucheton and Soulé, 2009 ; Saillot, 2015, 2018, 2020) taking into account different registers of concerns, and which can be modeled by a "systemic diamond" articulating four poles : THINK - SAY - DO - OBSERVE/LISTEN. We propose to understand the complexity of this activity by including this model in several moments (Lefebvre, 1973) themselves relating to various temporal levels of activity (Roquet, 2012). These help to define different scales of this adjustment posture. Analyzed from narratives of teaching practice, these moments also allow access to the strategic dimension of the posture of adjustment, in particular by declining the THINK pole of the systemic diamond into MOBILIZE-DESIGN-PROJECT.